Prawne problemy zaspokajania potrzeb mieszkaniowych w związku z zatrudnieniem w stosunku pracy: Legal problems that arise when housing needs connected with employment are met (Studia Prawnicze / The Legal Studies, 2023)
The article is an analysis of law on housing relations which genetically and functionally ensue from employment relations. The point of referrence is provid by Aricles 16 and 94 point 8 of the legal code, where an enterprise is put under an obligation to show concern that material, welfare and cultural needs of its employees are met. In author’s opinion this general obligation also embraces an obligatory concern about hosuing needs, which has also been specified by numerous unstatutory regulations. Firstly, these are common rights of all employees of state enterprises, under which they are entitled о financial benefits from the so called housing fund of enterprise. These are collective rights enjoyed by all employees. It is only after the housing fund has been divided, with the representative organs of employees participating, that individual rights come about.On the second level of the specification of the general housing committment of an enterprise there are particular regulations related to the selected groups of employees. These numerous regulations differ in respect of their normative rank, the date of enactment, and provide for a number of housing claims of varying contents and legal nature. As a result of meticulous analysis the the author makes a distinction, into three basic types of claims. The first group embraces housing benefits which are incorporated into the employment relations (e.g. free housing allowances). The second one contains the construction, where employment relations only provide for a possibility to require the execution of a housing claim, whereas the exercise of the claim takes place under a separate privity, e.g. lease. The third group comprises claims ensuing from other relations (recognizance or authoritative) than the employment ones, though entered into in connection with the latter while being employed at an enterprise and under the decision of the latter or any other competent subject.At the end of his article the author critically assesses the excessive differentiation and dispersal of legal provisions on housing relations that ensue from employment, and postulates that a separate and uniform act be passed in this respect.